Sectoral differences in the choice of the time horizon during estimation of the unconditional stock beta - Dimitrios Dadakas; Christos Karpetis; Athanasios Fassas; Erotokritos Varelas (International Journal of Financial Studies, 2016)
The stock beta coefficient literature extensively discusses the proper methods for the estimation of beta as well as its use in asset valuation. However, there are fewer references with respect to the appropriate time horizon that investors should utilize when evaluating the risk-return relationship of a stock. We examine the appropriate time horizon for beta estimation, differentiating our results by sector according to the Industry Classification Benchmark. We employ data from the NYSE and estimate varying lengths of beta employing data from 30 to 250 trading days. The constructed beta series is then examined for the presence of breaks using the endogenous structural break literature. Results show evidence against the use of betas that employ more than 90 trading days of data provisional to the sector under study.
Keywords: C10; C22; C59; G12; G19; 330; stock beta; endogenous structural breaks; time horizon